Dual-wavelength, mode-locked erbium-doped fiber laser employing graphene/polymethyl-methacrylate saturable absorber - Lau, Kuen Yao; Abu Bakar, Muhammad Hafiz; Muhammad, Farah Diana; Abd Latif, Amirah; Omar, Muhammad Firdaus; Yusoff, Zulfadzli; Mahdi, Mohd Adzir (Optical Society of America, 2018)
Mode-locked fiber laser incorporating a saturable absorber is an attractive configuration due to its stability and simple structure. In this work, we demonstrate a dual-wavelength passively mode-locked erbium-doped fiber laser employing a graphene/polymethyl-methacrylate saturable absorber. A laser resonator is developed based on dual cavity architecture with unidirectional signal oscillation, which is connected by a fiber branch sharing a common gain medium and saturable absorber. Dual wavelength mode-locked fiber lasers are observed at approximately 1530 and 1560 nm with 22.6 mW pump power threshold. Soliton pulse circulates in the laser cavity with pulse duration of 900 and 940 fs at shorter and longer wavelengths, respectively. This work presents a viable option in developing a low threshold mode-locked laser source with closely spaced dual wavelength femtosecond pulses in the C-band wavelength region.